A novel HBsAg-based model for predicting significant liver fibrosis among Chinese patients with immune-tolerant phase chronic hepatitis B: a multicenter retrospective study. (May 2021) - Zeng, Da-Wu; Huang, Zu-Xiong; Lin, Meng-Xin; Kang, Na-Ling; Lin, Xin; Li, Ya-Nan; Zhu, Yue-Yong; Liu, Yu-Rui
Background: Hepatitis B e antigen (HBeAg)-positive chronic hepatitis B (CHB) in the immune-tolerant (IT) phase is significantly associated with high risk for hepatocellular carcinoma, suggesting requirement for antiviral therapy, particularly for those with histological liver injury. This study aimed to establish a non-invasive panel to assess significant liver fibrosis in IT chronic hepatitis B. Patients and methods: One hundred and thirteen IT-phase CHB patients were retrospectively recruited and divided into two histopathological groups according to their histological profiles: necroinflammatory score <4 (N <4)/fibrosis score ⩽1 (F0-1), and necroinflammatory score ⩾4 (N ⩾4)/fibrosis score ⩾2 (F2-4). Multivariate analysis was conducted to assess the predictive value of the non-invasive model for significant liver fibrosis. Results: IT-phase CHB patients with N <4/F0-1 had significantly higher HBsAg levels than those with N ⩾4/F2-4. The optimal HBsAg level of log 4.44 IU/mL for significant liver fibrosis (F ⩾2) gave an area under the curve (AUC) of 0.83, sensitivity of 81.1%, specificity of 81.6%, positive predictive value (PPV) of 68.2%, and negative predictive value (NPV) of 89.9%. An IT model with HBsAg and gamma glutamyl transpeptidase (GGT) in combination was established, and it had an AUC of 0.86, sensitivity of 86.5%, specificity of 81.6%, PPV of 69.6, NPV of 92.5, and accuracy of 83.2% to predict F ⩾2 in the IT-phase CHB patients. Notably, the IT model exhibited higher predictive value than the existing aspartate aminotransferase-to-platelet ratio index, Fibrosis-4 score, and GGT to platelet ratio. Conclusion: The established IT model combining HBsAg and GGT has good performance in predicting significant liver fibrosis in IT-phase CHB patients.